Blood Cues Induce Antipredator Behavior in Nile Tilapia Conspecifics - Barreto, Rodrigo Egydio [UNESP]; Miyai, Caio Akira [UNESP]; Sanches, Fabio Henrique Carretero [UNESP]; Giaquinto, Percília Cardoso [UNESP]; Delicio, Helton Carlos [UNESP]; Volpato, Gilson Luiz [UNESP] (Public Library of Science (PLoS), 2013)
In this study, we show that the fish Nile tilapia displays an antipredator response to chemical cues present in the blood of conspecifics. This is the first report of alarm response induced by blood-borne chemical cues in fish. There is a body of evidence showing that chemical cues from epidermal 'club' cells elicit an alarm reaction in fish. However, the chemical cues of these 'club' cells are restricted to certain species of fish. Thus, as a parsimonious explanation, we assume that an alarm response to blood cues is a generalized response among animals because it occurs in mammals, birds and protostomian animals. Moreover, our results suggest that researchers must use caution when studying chemically induced alarm reactions because it is difficult to separate club cell cues from traces of blood. © 2013 Barreto et al.
Keywords: acclimatization; alarm monitoring; animal behavior; animal welfare; association; blood; chemical reaction; controlled study; defensive behavior; feeding; latent period; locomotion; nonhuman; Oreochromis niloticus; predation; Animal Communication; Animals; Avoidance Learning; Cichlids; Cues; Escape Reaction; Pheromones